Pengembangan Kecerdasan Musikal Anak di Taman Kanak-Kanak Pertiwi 3 Kantor Gubernur Padang - Indriani, Mutiya; Nurhafizah, Nurhafizah (Universitas Negeri Padang, 2024)
This research is carried out every day the implementation of activities carried out in Kindergarten Pertiwi 3 Of the Padang Governor's Office held knock play activities in the classroom so that every day children feel interesting activities and do not get bored for children for the development of children's musical intelligence. This research aims to get an overview of the development of early childhood musical intelligence in Kindergarten Pertiwi 3 Padang Governor's Office. This type of research is qualitative research using a descriptive approach. To see how the development of early childhood musical intelligence in Kindergarten Pertiwi 3 Padang Governor's Office. The subjects of the study were B3-graders at Kindergarten 3 of the Padang Governor's Office. The informant of this study is the principal and teacher in Kindergarten Pertiwi 3 Of the Padang Governor's Office. Data collection techniques are used in the form of observations, interviews, and documentation. Data analysis techniques are: 1) data collection, 2) data reduction, 3) presentation of data, 4) verification. While the data absorbing technique used in the form of triangulation techniques. The results of the study in general showed that in the development of early childhood musical intelligence in Kindergarten 3 the Governor's Office of Padang teachers has prepared a Daily Learning Implementation Plan (RPPH). Activities carried out every day have been done in accordance with what has been planned, activities carried out every day using various activities such as, playing beats, singing and others. Furthermore, after the child conducts teacher activities to conduct evaluations by means of observation and daily assessment.